ANALISIS PENDAPATAN USAHATANI SAYURAN DENGAN POLA TANAM TUMPANGSARI (Studi Kasus di Desa Gunung Lewat Kecamatan Suka Merindu Kabupaten Lahat) Analysis Of Vegetable Farming Income Production With Overlapping Planting Pattern (Case Study In Gunung Lewat Village Sub-district Sukamerindu Lahat District) - Saputra, Dimi; Iswarini, Harniatun; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2017)
ABSTRACT This study aimedto find how much income farmers from vegetable farming with various cropping patterns and to know which one intercropping pattern is more profitabble. This research has conducted in Gunung Lewat Villages trough districts Suka Merindu.  This research has conducted on March until May 2017.  This  research used survey method.  For sampling used census method, where in this study there are 14 farmers respondents.  Data collection methodsused in this research is observation with interview directly to responder which have been determined by using tool quisioner which have been prepared before.  Data processing used is the data obtained from the field first in the group and then processed by tabulation. From the results of the study showed planting pattern developed by farmers in Gunung Lewat Village very varied with the pattern of planting most is Cropping pattern  mustard-tomato-chili as much as 6 people or 42,84 percent and the least cultivation pattern in which the tomato, tomato-leaf, tomato-cabbage, tomato-chilli-bean long-leek, and tomato-aubergine as much as 1 person or 7,15 percent, while the pattern of planting tomato-chilli that is as many as 3 people or 21,41 percent. The largest average income of farmers is Rp 75.703.500 Lg / Th or Rp 1.849.962.500 Ha / Th while the smallest average income is Rp 4.817.500 Lg / Th or Rp 58.150.000 Ha / Th. The highest profit rate of the average farmers of respondents is 8,71 / Lg / Th or 4,12 / Ha / Th, while the lowest average profit rate of farmers of respondents is 1,82 / Lg / Th or 1,13 / Ha / Th with a favorable cultivation pattern of chili-tomato-leek planting pattern with a profit rate of 8,71 / Lg / Th or 4,12 Ha / Th.